Sentiment Analysis of Netizen's Comments on YouTube about IKN (Capital City) Development in Indonesia - Ilmatus Sa’diyah; Aviolla Terza Aviolla Terza; Cagiva Chaedar Bey Lima; Mohammad Rafka Mahendra Ariefean; Ikbar Athallah (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The National Capital City (IKN) of the Archipelago is located in North Penajam Paser Regency and Kutai Kartanegara Regency, East Kalimantan Province. The transfer and development of IKN does not only have an impact on moving the country's capital from Jakarta to Kalimantan, but also on the future development of IKN which includes social, economic, cultural and environmental aspects. This impact created sentiment in society. For this reason, this research was conducted to identify public sentiment towards IKN development in Indonesia through comments on YouTube. Data in the form of sentiment from public comments on YouTube which comes from data sources in the form of videos selected based on the highest total comments regarding IKN. Data was collected and analyzed using the Python system with stages of Web scraping, pre-processing, sentiment analysis, and classification methods. Based on the data analysis that has been carried out, positive sentiment, neutral sentiment and positive sentiment are distinguished. Meanwhile, positive sentiment can be seen from the words good and prosperous, negative sentiment can be seen from the words debt, corruption and pessimism, while neutral sentiment is related to prices, investors and toll money. This overall sentiment leads to rejection and acceptance of IKN development by the government. The reason is that the impact caused after the construction was a trigger for the emergence of comments on YouTube videos which led to public sentiment. The results of this analysis can be used as hope for the government to anticipate IKN development that will have a negative impact.